Integration of the Cloud Environment in E-Learning Systems - Dahdouh, Karim; Dakak, Ahmed; Oughdir, Lahcen (Transactions on Engineering and Computing Sciences, 2017)
Nowadays, e-learning systems have known a major revolution, especially with the emergence of new information and communication technologies and the enormous growth in the number of learners, educational content and resources. which causes many challenges in terms of optimizing resources such as compute, storage and communication, highlighting the need to use a model that meets evolving requirements and cost control. In this context, cloud computing is proving to be a promising model because of its permanent scalability and the efficient use of resources. This paper presents the characteristics of current e-learning systems, then analyzes the concept of cloud computing and describes the architecture of it by combining the features of e-learning. We propose an approach of using and harnessing Cloud computing services in e-learning systems to build an e-learning environment based on cloud computing.